2023
DOI: 10.1371/journal.pone.0280641
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol as a risk factor for hearing loss: A systematic review and meta-analysis

Abstract: Objective Growing evidence suggests that alcohol consumption is a risk factor for hearing loss; however, the evidence has been inconsistent. This systematic review and meta-analysis aimed to evaluate the effect of alcohol consumption on hearing loss. Methods We searched several databases up to November 2021, for published articles using the keywords “alcohol drinking” and “hearing loss”. Two investigators independently conducted the study selection and data extraction. Based on the results of the heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…A total of 10 meta-analysis studies were included in this study, which evaluated liraglutide, semaglutide, and tirzepatide for the treatment of obesity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 meta-analysis studies were included in this study, which evaluated liraglutide, semaglutide, and tirzepatide for the treatment of obesity [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…The estimated blood loss for this case was 300 cc, as per literature similar cases that do not undergo embolisation have an estimated blood loss of 450 cc. In fact, a retrospective study demonstrated that the estimated blood loss was higher in the embolised group (410 vs 315 mL, p=0.0074)1 and can range up to 691.43 cc 10…”
Section: Discussionmentioning
confidence: 98%
“… 22 , 23 One possible reason for this may be the stabilisation of sequencing or the methods used for establishing groups, which employed different ages, sex and smoking or drinking statuses. Qian et al 24 confirmed alcohol as a risk factor for hearing loss. Furthermore, in another study on the association between NIHL and gene analysis, the researchers found an association between NIHL and the rs41281334 of CDH23 , providing more evidence on the CDH23 gene and NIHL.…”
Section: Discussionmentioning
confidence: 98%